Synchronized mammalian cell culture: Part I—A physical strategy for synchronized cultivation under physiological conditions. (29th July 2014) - Barradas, Oscar Platas; Jandt, Uwe; Becker, Max; Bahnemann, Janina; Pörtner, Ralf; Zeng, An‐Ping
<x xml:space="preserve">Abstract</x> Conventional analysis and optimization procedures of mammalian cell culture processes mostly treat the culture as a homogeneous population. Hence, the focus is on cell physiology and metabolism, cell line development, and process control strategy. Impact on cultivations caused by potential variations in cellular properties between different subpopulations, however, has not yet been evaluated systematically. One main cause for the formation of such subpopulations is the progress of all cells through the cell cycle. The interaction of potential cell cycle specific variations in the cell behavior with large‐scale process conditions can be optimally determined by means of (partially) synchronized cultivations, with subsequent population resolved model analysis. Therefore, it is desirable to synchronize a culture with minimal perturbation, which is possible with different yield and quality using physical selection methods, but not with frequently used chemical or whole‐culture methods. Conventional nonsynchronizing methods with subsequent cell‐specific, for example, flow cytometric analysis, can only resolve cell‐limited effects of the cell cycle. In this work, we demonstrate countercurrent‐flow centrifugal elutriation as a useful physical method to enrich mammalian cell populations within different phases of a cell cycle, which can be further cultivated for synchronized growth in bioreactors under physiological conditions. The presented combined approach contrasts with other physical selection methods especially with respect to the achievable yield, which makes it suitable for bioreactor scale cultivations. As shown with two industrial cell lines (CHO‐K1 and human AGE1.HN), synchronous inocula can be obtained with overall synchrony degrees of up to 82% in the G1 phase, 53% in the S phase and 60% in the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1v5vdqc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />G2/M</alternatives> phase, with enrichment factors ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1v5vdpv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Ysync</alternatives>) of 1.71, 1.79, and 4.24 respectively. Cells are able to grow with synchrony in bioreactors over several cell cycles. This strategy, combined with population‐resolved model analysis and parameter extraction as described in the accompanying paper, offers new possibilities for studies of cell lines and processes at levels of cell cycle and population under physiological conditions. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:165–174, 2015